Economic analysis of cutandcarry, and alley cropping systems of mulch production for plantains in southeastern Nigeria - Ruhigwa, B.; Gichuru, M.; Spencer, D.; Swennen, Rony L. (1994)
Organic mulch is beneficial to plantain because it maintains soil fertility, prevents erosion and suppresses weeds. Mulch availability is however a major constraint. Mulching in a cut-and-carry system withPennisetum purpureum Schum. (elephant grass) was compared with mulching with the prunings ofAlchornea cordifolia (Schum. & Thonn.),Dactyladenia barteri (Hook. f. ex Oliv.)Engel. (Syn.Acioa barteri),Gmelina arborea (Roxb.) andSenna siamea (Lam.) Irwin & Barneby (Syn.Cassia siamea) in alley cropping systems. Plantain inPennisetum mulch treatment gave the highest bunch yield, but similar net revenues per hectare as theDactyladenia treatment, whileGmelina, Alchornea andSenna treatments produced the lowest incomes. But when the land required to producePennisetum mulch was included in the economic analysis, the net revenue per hectare was negative over three years of cropping. The returns to labour were also much lower for thePennisetum compared to the alley cropping systems. Among the in-situ mulch sources,Gmelina had the highest labour requirement because of the high pruning frequency. In addition, weeding inGmelina, Alchornea andSenna treatments resulted in high labour demand due to the rapid decomposition of the mulch materials leaving the soil bare for weeds to invade.Dactyladenia alley cropping was the most profitable of the five plantain production systems studied.